Peer-assisted teaching student tutors as examiners in an orthopedic surgery OSCE station – pros and cons - Melcher, Peter; Zajonz, Dirk; Roth, Andreas; Heyde, Christoph-E.; Ghanem, Mohamed (GMS Interdisciplinary Plastic and Reconstructive Surgery DGPW, 2016)
Background: The OSCE (objective structured clinical examination) is composed of oral and practical examination in order to examine students’ abilities to imply clinical examination techniques and to interact with patients. The examiners for this procedure can be either lecturers or peers. The aim of this work is to evaluate the peer-assisted teaching student tutors as examiners in an orthopedic surgery OSCE station. Methods: We analyzed the OSCE data from 2013 to 2015. During this period over 300 medical students were examined each year. An evaluation was conducted at an orthopedic station and examined by peer students to assess the advantages and disadvantages of peer-assisted teaching student tutors as examiners. Results: We have noticed that student peers are more flexible regarding their schedule and they have been well trained for OSCE. Concerning the economic aspects, student peers are clearly of major economic advantage.Disadvantages were not reported in our study probably because peers were well trained and the checklists are monitored regularly. Conclusion: Student peers in OSCE are of major advantage due to their flexible time schedule and relatively low costs. They must be well trained and the checklists are to be monitored regularly. Our study shows that peer tutor examiners conducted the examination as competent as lecture examiners. However, legal restrictions on the employment of students should be considered.